An Error Translation Used in “Pooh’s Neighborhood" Storybooks Children - Istiqomah, Lilik; Purwaningsih, Dewita; Permadi, Ryan (English Education: Jurnal Tadris Bahasa Inggris, 2019)
There is little research available on analyzing error translation in "Pooh's Neighborhood" Storybooks Children translated by an amateur translator Wahidah Muriska. This paper aims to analyze what kind of error that the translator made in the storybook. Error in translating not only causing misinformation in the target language but also appearing ambiguity into the readers perspective. After the researchers analyze the translation result, the researchers found some errors in words, phrases, clauses and sentences. The detail errors found in theose translations are modal, preposition, noun phrase, verb phrase, dependent and independent clause. The translator got difficulties in translating clause and phrase because most of error found in clause and phrase. The results show that error translation may appear because the translator lacks of reading whole text of expert translators. In the other opinion, the errors happen because the translator does not mastering the particular part of speechs in which error appear yet.